3D Structures of Plant Phytochrome A as Pr and Pfr From Solid-State NMR: Implications for Molecular Function - Song, Chen; Mroginski, Maria Andrea; Lang, Christina; Kopycki, Jakub; Gärtner, Wolfgang; Matysik, Jörg; Hughes, Jon (Frontiers in Plant Science, 2018)
We present structural information for oat phyA3 in the far-red-light-absorbing (Pfr) signaling state, to our knowledge the first three-dimensional (3D) information for a plant phytochrome as Pfr. Solid-state magic-angle spinning (MAS) NMR was used to detect interatomic contacts in the complete photosensory module [residues 1–595, including the NTE (N-terminal extension), PAS (Per / Arnt / Sim), GAF (cGMP phosphodiesterase / adenylyl cyclase / FhlA) and PHY (phytochrome-specific) domains but with the C-terminal PAS repeat and transmitter-like module deleted] auto-assembled in vitro with 13C- and 15N-labeled phycocyanobilin (PCB) chromophore. Thereafter, quantum mechanics/molecular mechanics (QM/MM) enabled us to refine 3D structural models constrained by the NMR data. We provide definitive atomic assignments for all carbon and nitrogen atoms of the chromophore, showing the Pfr chromophore geometry to be periplanar ZZEssa with the D-ring in a β-facial disposition incompatible with many earlier notions regarding photoconversion yet supporting CD data. The Y268 side chain is shifted radically relative to published Pfr crystal structures in order to accommodate the β-facial ring D. Our findings support a photoconversion sequence beginning with Pr photoactivation via an anti-clockwise D-ring Za→Ea photoflip followed by significant shifts at the coupling of ring A to the protein, a B-ring propionate partner swap from R317 to R287, changes in the C-ring propionate hydrogen-bonding network, breakage of the D272–R552 salt bridge accompanied by sheet-to-helix refolding of the tongue region stabilized by Y326–D272–S554 hydrogen bonding, and binding of the NTE to the hydrophobic side of ring A. We discuss phyA photoconversion, including the possible roles of mesoscopic phase transitions and protonation dynamics in the chromophore pocket. We also discuss possible associations between structural changes and translocation and signaling processes within the cell.